1999
DOI: 10.1016/s0014-5793(99)00729-2
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C‐θ is specifically activated in murine erythroleukaemia cells during mitosis

Abstract: Protein kinase C-a a is a member of the n-protein kinase C subfamily that in mitotic cells translocates to centrosomes and kinetochores. Although this kinase is expressed in comparable amounts in murine erythroleukaemia cells during the interphase or metaphase, when localized in the mitotic structures, it selectively phosphorylates a 66 kDa protein, also associated to chromosomes. Moreover, protein kinase C-a a immunoprecipitated from cells at the metaphase results four times more active in the absence of lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…Then, to rule out the occurrence of cytotoxic effects, cell growth, viability and apoptotic index have been measured. Cells treated with the PKC-antisense oligonucleotide display a 30% slower growth rate, in agreement with previous observations indicating a positive role for this kinase in the cell cycle progression (15). However, cell viability, evaluated by trypan blue exclusion staining, and the apoptotic index, determined with the acridine orangestaining (22), are not significantly modified.…”
Section: Effect Of Retinoic Acid In Lan-5 Cells Expressing Low Level supporting
confidence: 89%
See 3 more Smart Citations
“…Then, to rule out the occurrence of cytotoxic effects, cell growth, viability and apoptotic index have been measured. Cells treated with the PKC-antisense oligonucleotide display a 30% slower growth rate, in agreement with previous observations indicating a positive role for this kinase in the cell cycle progression (15). However, cell viability, evaluated by trypan blue exclusion staining, and the apoptotic index, determined with the acridine orangestaining (22), are not significantly modified.…”
Section: Effect Of Retinoic Acid In Lan-5 Cells Expressing Low Level supporting
confidence: 89%
“…In mitotic cells this kinase interacts with activating protein cofactors promoting the phosphorylation of chromosome protein targets (15). In different cell models, it has been demonstrated that PKC-associates to cell structures undergoing a dynamic reorganization (6,18,24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some PKC isoforms were also demonstrated to be mitotically activated (Goss et al, 1994;Thompson and Fields, 1996;Passalacqua et al, 1999), but mitotic PKC function remained largely unknown. We previously demonstrated that PKC phosphorylated vimentin by mitotic reorganization of intracellular membrane systems and the interaction of vesicles with vimentin ®laments (Takai et al, 1996).…”
Section: Discussionmentioning
confidence: 99%